Use of the Woven EndoBridge Device for Sidewall Aneurysms: Systematic Review and Meta-analysis - Rodriguez-Calienes, A.; Vivanco-Suarez, J.; Galecio-Castillo, M.; Zevallos, C.B.; Farooqui, M.; Malaga, M.; Moran-Mariños, C.; Fanning, N.F.; Algin, O.; Samaniego, E.A.; Pabon, B.; Mouchtouris, N.; et al. (American Journal of Neuroradiology, 2023)
BACKGROUND: The Woven EndoBridge device was originally approved to treat intracranial wide-neck saccular bifurcation aneurysms. Recent studies have suggested its use for the treatment of sidewall intracranial aneurysms with variable success.PURPOSE: Our aim was to evaluate the safety and efficacy of the Woven EndoBridge device for sidewall aneurysms using a meta-analysis of the literature.DATA SOURCES: We performed a systematic review of all studies including patients treated with the Woven EndoBridge device for sidewall aneurysms from inception until May 2022 on Scopus, EMBASE, MEDLINE, the Web of Science, and the Cochrane Central Register of Controlled Trials.STUDY SELECTION: Ten studies were selected, and 285 patients with 288 sidewall aneurysms were included.DATA ANALYSIS: A random-effects meta-analysis of proportions using a generalized linear mixed model was performed as appropriate. Statistical heterogeneity across studies was assessed with I2 statistics.DATA SYNTHESIS: The adequate occlusion rate at last follow-up was 89% (95% CI, 81%–94%; I2, = 0%), the composite safety outcome was 8% (95% CI, 3%–17%; I2 = 34%), and the mortality rate was 2% (95% CI, 1%–7%; I2 = 0%). Aneurysm width (OR = 0.5; P = .03) was the only significant predictor of complete occlusion.LIMITATIONS: Given the level of evidence, our results should be interpreted cautiously until confirmation from larger prospective studies is obtained.CONCLUSIONS: The initial evidence evaluating the use of the Woven EndoBridge device for the treatment of wide-neck sidewall intracranial aneurysms has demonstrated high rates of adequate occlusion with low procedural complications. Our findings favor the consideration of the Woven EndoBridge device as an option for the treatment of sidewall aneurysms.GCPgood clinical practiceNOSNewcastle-Ottawa Quality Assessment ScaleWEBWoven EndoBridge